Deciphering the role of trehalose in hindering antithrombin polymerization. Issue 4 (5th April 2019) - Naseem, Asma; Khan, Mohammad Sazzad; Ali, Hashim; Ahmad, Irshad; Jairajpuri, Mohamad Aman
Abstract : Serine protease inhibitors (serpins) family have a complex mechanism of inhibition that requires a large scale conformational change. Antithrombin (AT), a member of serpin superfamily serves as a key regulator of the blood coagulation cascade, deficiency of which leads to thrombosis. In recent years, a handful of studies have identified small compounds that retard serpin polymerization but abrogated the normal activity. Here, we screened small molecules to find potential leads that can reduce AT polymer formation. We identified simple sugar molecules that successfully blocked polymer formation without a significant loss of normal activity of AT under specific buffer and temperature conditions. Of these, trehalose proved to be most promising as it showed a marked decrease in the bead like polymeric structures of AT shown by electron microscopic analysis. A circular dichroism (CD) analysis indicated alteration in the secondary structure profile and an increased thermal stability of AT in the presence of trehalose. Guanidine hydrochloride (GdnHCl)-based unfolding studies of AT show the formation of a different intermediate in the presence of trehalose. A time-dependent fluorescence study using 1, 1′-bi(4-anilino)naphthalene-5, 5′-disulfonic acid (Bis-ANS) shows that trehalose affects the initial conformational change step in transition from native to polymer state through its binding to exposed hydrophobic residues on AT thus making AT less polymerogenic. In conclusion, trehalose holds promise by acting as an initial scaffold that can be modified to design similar compounds with polymer retarding propensity.